USING SCRATCH TO CREATE MULTIMEDIA-BASED MATERIAL IN TEACHING ENGLISH - Arini Kumala Sari; An Fauziah Syafei (Universitas Negeri Padang, 2013)
The purpose of this article is to explain how to use Scratch program to develop material of a descriptive text to Junior High School students. Material have a crucial rule for learning process. There are two ways to develop material: traditional and related to technologies. The lack of technology used for developing material is caused by the lack of knowledge and updated of the teacher for the use of new technologies, and the extremely hard of designing process. In contrast, there are some advantages for developing material that engage with new technologies. Learners tend to interest with pictures, animation and video that united with technology. So, learners can be attracted with entertainment atmosphere and activities while studying. It means teachers have opportunities to provide materials to learners for use outside the classroom and to learners who are otherwise unable to attend classes. Technologies may make possible to reduce the overall costs of developing language learning materials. Multimedia is a way to develop material through technology that can be engaged by video, sound, graph, animation and text. This paper will be focused to explain how to use Scratch to create multimedia-based material in listening, reading, speaking and writing a descriptive text to Junior High School students. The use of Scratch for developing material can be increased the learner’s interest to follow the learning process. Abstrak Tujuan penulisan artikel ini adalah untuk menjelaskan bagaimana cara menggunakan program Scratch dalam mengembangkan materi pembelajaran descriptive text kepada siswa SMP. Materi punya peranan penting dalam proses pembelajaran. Materi dapat dikembangkan secara tradisional dan berkenaan dengan teknologi baru. Kurangnya pengetahuan guru tentang penggunaan teknologi baru dan tidak ada nya pembaharuan guru tentang teknologi serta proses perancangan yang agak sedikit rumit menyebabkan kurangnya pengembangan materi pembelajaran yang berkenaan dengan teknologi ini. Padahal pengembangan materi dengan menggunakan teknologi punya banyak keuntungan. Salah satu nya dapat meningkatkan ketertarikan siswa melakukan aktivitas di dalam proses pembelajaran. Selain itu, guru juga punya kesempatan untuk mengembangan materi yang bisa digunakan di dalam kelas dan juga di luar kelas. Biaya yang digunakan untuk memperbanyak cetakan materi yang dibuat secara tradisional juga dapat dipangkas. Multimedia merupakan salah satu cara untuk mengembangkan teknologi dalam pembelajaran yang digabungkan dengan video, suara, grafik, animasi dan text. Salah satu software yang dapat menciptakan multimedia adalah Scratch. Makalah ini membahas tentang cara mengembangkan materi menggunakan Scratch dalam kemampuan mendengar, berbicara, membaca dan menulis sebuah teks deskriptive untuk siswa SMP. Penggunaan Scratch dalam mengembangkan materi diharapkan dapat meningkatkan ketertarikan siswa dalam mengikuti proses pembelajaran.